FOMO and Interactive Live Streaming on Customer Loyalty TikTok: Moderating Role of Pocket Money and Perceived Ease of Use - Ismayudin Yuliyzar; Cahyani Kurniastuti; Nursimah Dara; Abdul Rauf; Hendra Galuh Febrianto; Mona Fairuz Ramli (Universitas Mercu Buana, 2026)
The explosive growth of TikTok Live Shop in Indonesia has made understanding the drivers of impulse buying among young consumers a research priority of urgent importance. This study examines how psychological factors, such as Fear of Missing Out (FOMO), and platform features, including Interactivity, influence impulsive purchasing decisions, while also considering the moderating roles of financial constraints (allowance) and user experience (perceived ease of use). Data was collected from university students in Tangerang and analyzed using Structural Equation Modeling (SEM). The results confirm that both FOMO and Interactivity are significant drivers of impulse buying. Notably, the study reveals that a user-friendly platform and higher disposable allowance can intensify these effects. The research offers a novel contribution by integrating financial and technological moderators into a single framework for live streaming commerce, providing critical insights for marketers, platform designers, and consumer protection advocates seeking to navigate the ethical complexities of this rapidly evolving digital marketplace.